Physical activity as a component of students' life quality. - Pavlova Iu.A; Tulaydan V.G; Vynogradskyi В.A (Kharkov National Pedagogical University, 2011)
The model of students' life quality and its basic components were described. Among this components are: objective (level of physical fitness and daily physical activity, financial status, opportunities to improve professional skills or obtain a certain academic level, etc.) and subjective (health, satisfaction with own lives, optimism, feeling of happiness, tasks and results, relationships with others, etc.). The positive influence of physical training on physical and mental capacity of students were investigated.